IMPLIKASI RISET AKUNT ANSI KEPERILAKUAN TERHADAP PENGEMBANGAN AKUNT ANSI MANAJEMEN - Sujadi, Sujadi (JURNAL STIE SEMARANG, 2011)
Behavioral    accounting    research    (behavioral    accounting    research   /   BAR)   is   an emerging    research   field.    Behavioral    accounting    research    in   the  field    of   management accounting   such  as budgeting   research  is initiated  by Argyris  (1952)  who  conducted  a field study  about  the budget process.  In the present  development  of accounting  behavioral  research in  the field   of  management   accounting   has  developed   in  the  research  and  testing  of  new concepts  in management   accounting.   The results  of behavioral  accounting  research  is to test new   concepts   in  management    accounting   such   as  activity   based   management.   customer orientation,    cross-functional    perspective.    total   quality   management.    time   as   competitive element.  and  E-business   efficiency,  the ABC  system.  and  the balanced  scorecard  is expected will provide   a development   of  theories  of management  accounting   to be a better  theory  and believed   its  implementation    would   benefit   the  company.   Through   behavioral   accounting research  in management  accounting  is expected  to give birth a new concept or theory.